2018
DOI: 10.1167/iovs.17-23376
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hyperglycemia, Evidence for Retinal Neurodegeneration in Metabolic Syndrome

Abstract: The patients with MetS had thinner inner retinal layers and photoreceptor layer in OCT segmentation analysis, which suggests that inherent factors of MetS, such as insulin resistance and adipose tissue-derived inflammation, might have a neurodegenerative effect independent of the hyperglycemic levels associated with DM. Therefore, beyond glycemic control measures, weight reduction also might be advised to overweight patients with type 2 DM and MetS to prevent the occurrence of retinal neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Furthermore, postmortem human samples and in vivo OCT data show evidence that progressive cell death may eventually lead to the thinning of the retinal layers. Specifically, the inner retinal layers and ganglion cells are thought to be the most vulnerable 50 . According to some human OCT data, loss of ganglion cells may be the first morphological sign of diabetes, preceding clinically detectable vasculopathy 51,52 or even present in metabolic syndrome 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, postmortem human samples and in vivo OCT data show evidence that progressive cell death may eventually lead to the thinning of the retinal layers. Specifically, the inner retinal layers and ganglion cells are thought to be the most vulnerable 50 . According to some human OCT data, loss of ganglion cells may be the first morphological sign of diabetes, preceding clinically detectable vasculopathy 51,52 or even present in metabolic syndrome 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…Karaca et al reported that the patients with metabolic syndrome have inner and outer retinal thinning on OCT segmentation analysis. They investigated the retinal neurodegenerative factors in patients with metabolic syndrome other than hyperglycemia and speculated that IR, low grade sytemic inflammation and hypertension-related endothelial damage might have a neurodegenerative effect independent of the hyperglycemia [11].…”
Section: Recentmentioning
confidence: 99%
“…IR was found to cause neuroinflammation and have a role in the pathophysiological mechanisms of some neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, multiple sclerosis and schizophrenia [10]. In recent clinical studies, beyond hyperglycemia, IR itself was shown to cause retinal nerve fiber layer thinning and ganglion cell loss in patients with metabolic syndrome [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The retinal nerve fiber layer (RNFL) is the innermost retinal neural layer consisting of the unmyelinated axons of the retinal ganglion cells, making it ideal for assessment of central nervous system health and possible neurodegeneration [7]. The macula is the central 5 mm of the posterior pole, consisting of the fovea, a 1 mm-in-diameter area centered around a central depression called the foveola, specialized for high spatial acuity and color vision; the parafoveal area, a 2 mm wide ring surrounding the fovea, where the ganglion cell layer, inner nuclear layer, and outer plexiform layer are thickest; and the perifoveal zone, a ring approximately 2 mm wide next to the parafoveal area [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced RNFL and macular thickness have been shown to occur in many metabolic diseases such as obesity, diabetes mellitus, and hypertension. Karaca et al found reduced thickness in the inner layers of various areas of the macula in 29 eyes of MetS patients compared to controls [7]. Laiginhas et al found reduced RNFL thickness in obese patients going for bariatric surgery [9].…”
Section: Introductionmentioning
confidence: 99%